Self-Associations Influence Task-Performance through Bayesian Inference - Bengtsson, Sara L.; Penny, William D. (Frontiers in Human Neuroscience, 2013)
The way we think about ourselves impacts greatly on our behaviour. This paper describes a behavioural study and a computational model that sheds new light on this important area. Participants were primed 'clever' and 'stupid' using a scrambled sentence task, and we measured the effect on response time and error-rate on a rule-association task. First, we observed a confirmation bias effect in that associations to being 'stupid' led to a gradual decrease in performance, whereas associations to being 'clever' did not. Second, we observed that the activated self-concepts selectively modified attention towards one's performance. There was an early to late double dissociation in RTs in that primed 'clever' resulted in RT increase following error responses, whereas primed 'stupid' resulted in RT increase following correct responses. We propose a computational model of subjects' behaviour based on the logic of the experimental task that involves two processes; memory for rules and the integration of rules with subsequent visual cues. The model also incorporates an adaptive decision threshold based on Bayes rule, whereby decision thresholds are increased if integration was inferred to be faulty. Fitting the computational model to experimental data confirmed our hypothesis that priming affects the memory process. This model explains both the confirmation bias and double dissociation effects and demonstrates that Bayesian inferential principles can be used to study the effect of self-concepts on behaviour.